Formulation of a Single Selective Culture Medium for the Enumeration of Lactic Streptococci and Lactobacilli from Fermented Milk Products - Gopal S.; Shashikumar C. S.; Yadav S. K.; Prabha R. (Current Perspectives in Agriculture and Food Science Vol. 8, 2024)
Background: Lactic acid bacteria are among the most important groups of microorganisms used in food fermentation. Enumeration of mixed lactic flora like lactic streptococci and lactobacilli may be difficult using a single culture medium. Aims: The present study is focused on formulating a single selective differential medium for the enumeration of mixed lactic flora such as lactic streptococci and lactobacilli in domestic and market fermented milk products. Methodology: In order to enumerate lactic streptococci and lactobacilli in a mixed flora of fermented milk, the formulation of a single selective medium was optimized using inhibitors and indicators instead of a separate selective medium for lactic streptococci and lactobacilli. The present study was conducted in the Department of Dairy Microbiology, Dairy Science College, Karnataka Veterinary, Animal and Fisheries Sciences University (KVAFSU), Hebbal, Bengaluru-24, Karnataka from February 2020 to February 2021. Fermented milk samples like curd, and yoghurt were collected, serially diluted, and pour-plated using Readymade M17 and MRS agar media and formulated selective yeast glucose agar medium. Lactic colonies obtained were enumerated, expressed as log10cfu/g, and the critical difference was calculated to declare significance and non-significance among the microbial parameters. Results: Readymade M17 and MRS agar media gave better recovery of viable cells of lactic streptococci and lactobacilli from market samples of curd, yoghurt, and domestic curd samples. The study helped to convert a general-purpose medium yeast glucose agar as a selective differential medium with the addition of calcium propionate of 0.8 per cent to avoid Bacillus spore formers and sodium benzoate of 1.2 per cent to inhibit yeast, the common contaminants in fermented milk with 0.05 per cent BCP that led to the formation of purple colonies of lactic streptococci and yellow colonies of lactobacilli. Conclusion: The readymade medium for lactic streptococci M17 agar medium gave better results when compared to the formulated medium. The selective yeast glucose agar with 0.8 per cent and sodium benzoate of 1.2 per cent with 0.05 per cent BCP with purple colonies of lactic streptococci and yellow colonies of lactobacilli can be successfully used. This study verified the enumeration of mixed lactic flora in fermented milk products instead of M17 medium for lactic streptococci and MRS for lactobacilli, separately.